Enzymatic Hydrolysis of Cephalosporin C by an Extracellular Acetylhydrolase of Cephalosporium acremonium - Hinnen, A. (1976)
Extracellular hydrolases from Cephalosporium acremonium were analyzed according to their ability to deacetylate the β-lactam antibiotic cephalosporin C. One out of at least six hydrolases exhibits appreciable cephalosporin C acetylhydrolase (CAH) activity. This enzyme was separated from other hydrolases and purified 220-fold. The purified CAH has a relatively low affinity for cephalosporin C (K(m), 20 mM) and is strongly inhibited by diisopropylfluorophosphate and less markedly affected by fluoride. Addition of glucose, maltose, and sucrose to the culture broth suppresses CAH production, whereas glycerol and succinate have no effect. Verrucarin A prevented the enzyme from appearing in the medium, which indicates the necessity of protein synthesis for CAH formation. When 1-thio-d-glucose was added to the culture medium, the results suggested that this glucose analogue is able to inhibit CAH synthesis. Our data provide evidence for a regulation of CAH synthesis similar to the catabolite repression system in bacteria.